2018
DOI: 10.3389/fneur.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Abduction Loading Therapy with Horizontal-Plane Viscous Resistance Targeting Weakness and Flexion Synergy to Treat Upper Limb Function in Chronic Hemiparetic Stroke: A Randomized Clinical Trial

Abstract: BackgroundProgressive abduction loading therapy has emerged as a promising exercise therapy in stroke rehabilitation to systematically target the loss of independent joint control (flexion synergy) in individuals with chronic moderate/severe upper-extremity impairment. Preclinical investigations have identified abduction loading during reaching exercise as a key therapeutic factor to improve reaching function. An augmentative approach may be to additionally target weakness by incorporating resistance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 43 publications
5
40
0
Order By: Relevance
“…In either scenario, however, this finding supports the hypothesis that the descending neuromodulatory component of the PMRF plays a key role in enabling vigorous expression of the flexion synergy. This finding also provides compelling evidence for the progression toward early phase clinical trials investigating both the independent effects of TIZ on motor function and the augmentative effects of TIZ in combination with physical interventions designed to target flexion synergy ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In either scenario, however, this finding supports the hypothesis that the descending neuromodulatory component of the PMRF plays a key role in enabling vigorous expression of the flexion synergy. This finding also provides compelling evidence for the progression toward early phase clinical trials investigating both the independent effects of TIZ on motor function and the augmentative effects of TIZ in combination with physical interventions designed to target flexion synergy ( 39 , 40 ).…”
Section: Introductionmentioning
confidence: 70%
“…It is noteworthy that the positive impact of TIZ on work area persisted even as shoulder abduction loading increased to 50% of maximum, because it suggests that mechanism-based pharmacotherapies may improve function over a wide range of exertion levels associated with activities of daily living. Previously, our laboratory has shown that a mechanism-based physical rehabilitation intervention consisting of an 8-week training protocol centered about progressive re-introduction of shoulder abduction loading during reaching could also drive significant increases in work area ( 39 , 67 ) and reaching distance ( 40 ). Considering the apparent functional impact of the present study, advancement of the pharmaceutical approach to early-phase clinical trials is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure could have a significant impact on future neuropathophysiological studies on individuals with an unilateral brain injury, since recent studies have indicated that motor impairments after a unilateral brain injury could be associated with an increased reliance on multi-synaptic indirect motor pathways following a lesion-induced loss of direct corticospinal projections (Owen et al, 2017;McPherson et al, 2018a;Karbasforoushan et al, 2019). Therefore, a measure that quantitatively determines the usage of indirect motor pathways over direct corticospinal drive could be crucial (1) for evaluating motor recovery following unilateral brain injuries, and (2) for determining the effect of targeted therapeutic interventions (Ellis et al, 2018;McPherson et al, 2018b) that aim to reduce the maladaptive reliance on indirect motor pathways after a hemiparetic stroke. In the future, we will examine both crossfrequency and iso-frequency coupling, as well as the COI, between the brain and muscle signals to characterize the relative ratio of the recruitment of indirect vs. direct motor pathways following unilateral brain injuries, such as hemiparetic stroke and unilateral celebral palsy.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly possible; however, we have previously demonstrated the ability for even those individuals with severe motor impairments to re-engage remaining resources in the lesioned hemisphere and improve hand function following device-assisted training (Wilkins et al 2017). Considering that it is also possible to reduce the flexion synergy through progressive SABD training (Ellis et al 2009;Ellis et al 2018), future work targeting both the flexion synergy and finger/wrist extensor weakness may yield a solution with respect to improving both hand and upper extremity function via a re-engagement of remaining ipsilesional resources, at least for individuals following the observed neural-behavioural pattern found here.…”
Section: Discussionmentioning
confidence: 99%